2013
DOI: 10.2514/1.c032316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Freeplay on Dynamic Stability of an Aircraft Main Landing Gear

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Considering the desirable case where no shimmy occurs we define the set of allowable freeplay profiles that satisfy a conservative stability criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 8 publications
(12 reference statements)
1
34
0
Order By: Relevance
“…Clearly, the original nonlinear system equations scale with freeplay, and this carries over to the HB formulation since F 1 is a function of θ∕θ fp . This scaling is observed even in a landing gear study with multiple nonlinearities of which freeplay is the dominant one [10], and it has been experimentally verified for the aeroelastic system of [8]. Note that the equations also scale in the presence of multiple freeplay if the ratios of the freeplay values are fixed.…”
Section: Stepmentioning
confidence: 66%
“…Clearly, the original nonlinear system equations scale with freeplay, and this carries over to the HB formulation since F 1 is a function of θ∕θ fp . This scaling is observed even in a landing gear study with multiple nonlinearities of which freeplay is the dominant one [10], and it has been experimentally verified for the aeroelastic system of [8]. Note that the equations also scale in the presence of multiple freeplay if the ratios of the freeplay values are fixed.…”
Section: Stepmentioning
confidence: 66%
“…The freeplay that we consider here takes the form of a lateral play in the landing gear torque links (a typical source of landing gear freeplay) which, via the system geometry, results in a torsional play. In [7] we found that freeplay of this form has a significant effect on landing gear stability, and we observed a multitude of resulting oscillatory phenomena. Furthermore, we also found the characteristics of freeplay to be influential on the observed behaviour with 'sharper' freeplay profiles allowing shimmy oscillations over more typical operating conditions.…”
Section: Introductionmentioning
confidence: 68%
“…In this work we focus on the dynamic stability of an aircraft dual-wheel main landing gear (MLG) and use the technique of numerical continuation to perform a bifurcation analysis, exploring its nonlinear dynamics. We bring together several key concepts from the earlier studies [7,8] and, in particular, focus on the the combined effects of mechanical freeplay and geometric coupling. Taken individually, these subjects formed the basis for the two earlier papers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The work by Howcroft et al [12] indicates that the translational freeplay of the order of 10 0 mm introduced at the torque link apex produces an angular freeplay of the order of 10 À 1 degrees. Fig.…”
Section: Freeplaymentioning
confidence: 98%